Pengaruh Komponen Pariwisata Terhadap Minat Berkunjung Kembali di Taman Bukit Siguntang Palembang, Sumatra Selatan - Orindia, Orindia; Maharani, Mira; Abduh, Mohammad Syaltut (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan DigitalDO - 10.30647/jpbd.v2i2.2107, 2026)
This study aims to analyze the effect of tourism components on tourists’ intention to revisit Taman Bukit Siguntang, Palembang, South Sumatra. A quantitative approach with a survey method was employed. Primary data were collected through questionnaires distributed to 100 tourists who had previously visited Taman Bukit Siguntang, while secondary data were obtained from relevant literature and supporting documents. Tourism components were measured through attractions, amenities, accessibility, and ancillary services, while revisit intention was measured based on the intention to revisit and recommend the destination. The data were analyzed using simple linear regression with the assistance of SPSS version 27. The results indicate that tourism components have a positive and significant effect on tourists’ revisit intention, with a regression coefficient of 0.308, a t-value of 25.045, and a significance level of 0.001. The R-square value of 0.865 indicates that tourism components explain 86.5% of the variance in tourists’ revisit intention. These findings highlight the importance of improving the quality of tourism components to encourage repeat visits to Taman Bukit Siguntang. Keywords: tourism components, revisit intention